PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN: (Pada Perusahaan Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2015-2020) - Heru Satria Rukmana; Muhlis Muhlis; Zeze Zakaria Hamzah; Annisa Apriyanti (Institut Teknologi dan Bisnis Dewantara, 2022)
This research was conducted to determine the effect of financial ratios on firm value. The variables in this study consisted of independent variables, namely the current ratio, debt to equity ratio, return on assets, and total asset turnover, while the dependent variable was the value of the food and beverage sector companies listed on the Indonesia Stock Exchange. The population in this study were all food and beverage sector companies listed on the Indonesia Stock Exchange during the 2015-2020 period. The sample selection used purposive sampling technique. The number of samples obtained as many as 10 companies. The data were analyzed by multiple linear regression method. The results of this study are the disclosure of the effect of current assets, debt to equity ratio, return on assets, and total asset turnover on firm value. significance 0.386 so that Ha1 is rejected; the variable debt to equity ratio (DER) has a positive and significant effect on firm value, as evidenced by the t-count result of 10,427 and a significance of significant effect on firm value, as evidenced by the t-count result of 2.782 with a significance of 0.007 so that Ha2 is accepted; the return on assets (ROA) variable has a positive and 0.000 so that Ha3 is accepted; The total asset turnover variable has a negative and significant effect as evidenced by the t-count result -2.091 with a significance of 0.041 so that Ha4 is rejected.